Tragedy “Mozart and Salieri”: Conflict Phenomenology and Culturology - P. N. Tolstoguzov (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The questions linked with originality of the conflict in Pushkin’s tragedy “Mozart and Salieri” are considered. The relevance of the study is due to the extreme complexity and fundamental controversy of Pushkin’s position in the genre search of the era. Special attention is paid to the phenomenological and cultural aspects of the conflict. On the part of phenomenology, the conflict is characterized as “inconsistent” and thus achieves extraordinary vitality against the background of the era. It is shown that this is a conflict that is brought into the consciousness of one hero (Salieri) and that constantly changes its characteristics. On the part of culturology, the conflict is characterized by the involvement of mixed features of classical and romantic literature. In addition, it has long been noted that it is complicated by the connection of complex cultural contexts. In particular, two contexts are additionally involved in the analysis in the article: musical-genre disputes of the 18th century and contrasting masks (Heraclitus and Democritus). The author comes to the conclusion that Mozart and Salieri are not antagonists in the spirit of the classical antinomy of characters and beliefs: they are a two-dimensional unity (both being “the sons of harmony”), composed of intuitive genius and deep rationalism, the latter within the boundaries of romantic anthropology most convincingly revealed through “villainy”.